Comparison of the composition, immunological activity and anti-fatigue effects of different parts in sika deer antler - Chen, Siqi; Li, Yidan; Yang, Yichun; Zhao, Shibo; Shi, Huali; Yang, Chengkai; Wu, Min; Zhang, Aiwu (Frontiers in Pharmacology, 2024)
BackgroundSika deer (Cervus nippon Temminck, 1838) antler is a highly esteemed tonic renowned for its abundant assortment of polypeptides, polysaccharides, amino acids, and minerals, and is recognized for its multifarious pharmacological properties. However, limited research has been conducted regarding the variation in composition of deer antlers between the upper and basal sections, as well as their pharmacological effects on immunological activity and anti-fatigue in mice. The objective of this study was to conduct a comprehensive analysis on the appearance, chemical composition, and pharmacological effects of different components within sika deer antlers. This investigation aims to elucidate the disparities in quality among various parts of antlers and establish a theoretical foundation for the precise utilization of sika deer antlers.MethodsThe contents of protein, amino acids, polysaccharides, phospholipids, minerals and nucleotides in wax, powder, gauze and bone slices were determined by different nutrient assays. Then, 100 mice were randomly divided into 5 groups. The mice in control group were administered 0.3 mL of saline solution per day. The mice in experimental groups were administered 0.3 mL enzymatic hydrolysate of the wax slice, powder slice, gauze slice, bone slice separately per day, continuously for 14 days from the first day. The effect of antler on boosting immunity was evaluated by testing organ indices and assessing immunoglobulin levels by ELISA. Anti-fatigue effects were assessed by a mouse swimming test. Finally, the correlation between composition and pharmacological effects was analysed.ResultsThe content of each marker substance gradually decreases from the upper to the basal of deer antler. The protein and uracil content in the wax slice were significantly higher than the other three groups (p < 0.05), and the phospholipid and inosine content were strongly significantly higher than the other three groups (p < 0.01). The content of polysaccharides and hypoxanthine in the wax slice group and powder slice group was significantly higher than that in the gauze slice group and bone slice group (p < 0.05). The amino acid content decreases from the upper to the basal section. Among, the content of Glu, Gly, His, and Pro wax slice was significantly higher than the other three groups (p < 0.01). The content of other minerals except Fe and Mg in the wax slice group was significantly higher than the other three groups (p < 0.01), and the content of Fe and Mg in the bone slice was the highest. Additionally, the immune organ index, immunoglobulin, and glycogen contents displayed a significant increase in comparison to both the control group and the other experimental groups (p < 0.05). And the swimming endurance of mice in the wax slice group was significantly prolonged (p < 0.01). The skeletal muscle state of the wax group mice exhibited superior characteristics, characterized by distinct horizontal stripes and tightly arranged muscle fibers. In contrast, the bone group displayed noticeable yet relatively less compact horizontal stripes. Among the organic and inorganic compositions of deer antler, the highest degree of correlation with the content of IgA, IgM, and IgG was found to be protein (r2 = 0.999), uracil (r2 = 0.987), and inosine (r2 = 0.999), respectively. The proteins (r2 = 0.997) appear to exert a significant influence on the anti-fatigue effect, while polysaccharides (r2 = 0.865) demonstrate the least relevance.ConclusionThese outcomes indicated that the wax slice yielded optimal results among the tested parts and demonstrated the highest efficacy.